The relationship between mesoscale deformation-induced surface roughness, in-plane plastic strain and texture sharpness in an aluminum alloy. (July 2022) - Romanova, V.; Balokhonov, R.; Zinovieva, O.; Shakhidzhanov, V.; Dymnich, E.; Nekhorosheva, O.
Highlights: Mesoscale deformation-induced roughening in Al1050 is studied experimentally and numerically. Relative roughness parameter Rd is a ratio of the surface profile length to the base line. The Rd values correlate exponentially with in-plane plastic strains at mesoscale. A sharp cube texture suppresses orange peel pattern but intensifies larger-scale waviness. Abstract: Experimental and numerical studies are performed to reveal an interrelation between mesoscale deformation-induced surface roughening and in-plane plastic strain in an aluminum alloy. Experimentally, roughness evolution in selected subsections of a uniaxially loaded specimen is examined using a stop-and-study technique. The experimental analysis is complemented by the micromechanical simulations for deformation-induced surface roughening in model polycrystals, with special attention being given to the texture effect on roughness characteristics. The experimental and numerical roughness patterns are analyzed in terms of a relative roughness parameter calculated as a ratio of the rough profile length to the profile evaluation length. This parameter is found to correlate exponentially with in-plane plastic strain with the coefficient of determination 0.99, which implies a strong interrelation between the two quantities. The results prove the assumption that in-plane plastic strains accumulated in a loaded material can be evaluated from the estimations of mesoscale surface roughness.